Miss Jessie Austin Honored by Associates from CMA - Vallejo News Chronicle (Vallejo News Chronicle)
Miss Jessie Austin, retiring after 25 years as a bookkeeper at the California Maritime Academy, was honored by friends and business associates at a retirement dinner held in Pappy's Restaurant, Amercian Legion Post 104, recently.